2008
DOI: 10.1021/la8022425
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ethanol on the Micellization and Gelation of Pluronic P123

Abstract: In certain applications copolymer P123 (E21P67E21) is dissolved in water-ethanol mixtures, initially to form micellar solutions and eventually to gel. For P123 in 10, 20, and 30 wt % aqueous ethanol we used dynamic light scattering from dilute solutions to confirm micellization, oscillatory rheometry, and visual observation of mobility (tube inversion) to determine gel formation in concentrated solutions and small-angle X-ray scattering (SAXS) to determine gel structure. Except for solutions in 30 wt % aqueous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
55
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 57 publications
8
55
2
Order By: Relevance
“…We note that broadly consistent results have been reported for gels of related Pluronic copolymers in ethanol/water solutions, e.g. P123 (E 21 P 67 E 21 ) [10][11][12], P105 (E 37 P 58 E 37 ) [13] and F88 (E 97 P 39 E 97 ) [14].…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…We note that broadly consistent results have been reported for gels of related Pluronic copolymers in ethanol/water solutions, e.g. P123 (E 21 P 67 E 21 ) [10][11][12], P105 (E 37 P 58 E 37 ) [13] and F88 (E 97 P 39 E 97 ) [14].…”
Section: Introductionsupporting
confidence: 89%
“…A similar increase in particle size with increase in alcohol concentration has been observed by Bharatiya et al for copolymer P123 in aqueous solutions of various alkanols, and has been ascribed to solvation of the alcohols by the micelles [17]. Swelling of the cores of the micelles of related copolymers is known to lead to formation of elongated (wormlike) micelles [12] and, given recent evidence of the formation of such micelles in dilute solutions of F127 in water [18], this may be so in the present case.…”
Section: Dynamic Light Scatteringsupporting
confidence: 75%
“…For Brij 78, these solutions were in 20% DMSO-d 6 -80% D 2 O (v/v) and for The CMC behavior of various PEO-block copolymers has been investigated in water-ethanol mixed solvents. [33][34][35] These studies have shown that the CMC increased aer addition of ethanol. The addition of DMSO-d 6 to D 2 O seems to show the same tendency, providing better solvent conditions for the Brij 78 and 98 compared to pure D 2 O and disfavoring the formation of micelles (self-assembly).…”
Section: Resultsmentioning
confidence: 97%
“…As described previously for solutions of P123 in aqueous ethanol [10], the onset of turbidity can be assigned to the formation of elongated micelles. Any additive which enlarges the cores of spherical micelles, whether by solubilization in the core or by modifying the water structure in such a way as to increase the association number (N) of the micelles, can cause overstretching of the core chains and promote the sphere-to-cylinder transition.…”
Section: Turbidity and Clouding: 1 Wt% P123mentioning
confidence: 75%
“…We associate the formation of turbid fluids at higher temperatures with the formation of worm-like micelles, as discussed in Section 3.1. Worm-like micelles have been identified in a closely related turbid fluid, 11 wt.% P123 in 10 wt.% ethanol/ water at 55°C, by observation of the characteristic plateau region in its flow curve [10], and elongated micelles have been confirmed in other solutions of P123 in ethanol/water by use of scattering and viscometric techniques [14].…”
Section: Gel Diagramsmentioning
confidence: 94%